A life cycle assessment of the construction phase of eleven micro-hydropower installations in the UK. (1st May 2019) - Ueda, T.; Roberts, E.S.; Norton, A.; Styles, D.; Williams, A.P.; Ramos, H.M.; Gallagher, J.
Abstract: The rapid deployment of renewable energy technologies continues, yet the environmental impacts associated with their construction is accepted without sustainable design considerations. This life cycle assessment study quantifies the embodied burdens in the construction phase of eleven micro-hydropower installations, ranging from 70–100 kW in size. The consumption of concrete and aggregates, metals and plastics influence each of the five impact categories assessment differently. In relation to global warming potential, upstream production of concrete and aggregates contributed 25–44%, whilst production of plastics contributed 27–49%. For acidification potential, production of metals and plastics contributed 29–67% and 19–45%, respectively. Production of metals used in MHP projects contributed 86–98% of human toxicity potential and 79–98% of abiotic resource depletion, whilst production of plastics contributed 56–77% of fossil resource depletion potential. One low-head scheme had the highest global warming, acidification and fossil resource depletion burdens due to large quantities of materials used in construction, while another scheme demonstrated high human toxicity and abiotic resource depletion burdens due to a 3-km grid connection upgrade for exporting electricity. The results were more sensitive to the quantity of materials used in the micro-hydropower projects than to changes in transport and construction contributions. The use of alternative materials could reduce global warming potential, e.g. a wood-frame powerhouse instead of concrete construction would reduce it by 6–12%. The results also indicated a general trend of reduced burdens per kWh electricity generated as capacity increased. However, no clear correlations were found between site-specific characteristics and environmental impacts in constructing these micro-hydropower projects. Therefore, independent life cycle assessment case studies are still required to inform better construction practices for specific renewable energy projects, with significant potential to improve environmental performance, especially in relation to resource efficiency as per circular economy principles. Graphical abstract: Image 1 Highlights: The life cycle construction burdens for eleven micro-hydropower installations are presented. The predominant embodied burdens relate to concrete and aggregates, metals and plastics. The most materials and highest GWP, AP and FRDP burdens occur at low head sites. High HTP and ARDP burdens were due to the requirement of a grid connection upgrade. No simple method for estimating MHP environmental impacts can be generated.